The use of impact bed breakage procedure in model fitting of dry stirred mill. (2nd October 2020) - Altun, Deniz; Altun, Okay; Benzer, Hakan
Abstract: This paper aimed to investigate the applicability of impact bed breakage test for model fitting of continuous dry horizontal stirred mill. Initially, the breakage tests were performed for three types of materials at varying bed diameters, 2 cm, 3 cm, 4 cm, and 6 cm to find out the optimal bed geometry. The test results for the three materials showed that the bed height of 4 cm was optimal as the fines' generation reached to a plateau and decided to be used in model fitting of the dry stirred mill. Afterward, cement material was processed within the dry stirred mill and samples were collected from feed and product ends when the steady-state conditions were established. The results of the grinding tests on cement material together with its breakage results obtained from 2 cm and 4 cm diameter beds were used in the model fitting of the mill by using perfect mixing approach. Accurate model fitting was obtained in case 4 cm diameter of bed was utilized and the predictions were in good agreement with the measured size distributions even if the operating conditions of the mill were changed.